HUBUNGAN ANTARA STATUS KESEHATAN ORAL DENGAN KUALITAS HIDUP BERDASARKAN KESEHATAN ORAL MASYARAKAT LANJUT USIA DI KODYA YOGYAKARTA - , Dewi Agustina ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background : quality of life assessment mostly is based on general health of people. In fact, oral health might play a significant role in determining the quality of life of someone. Deterioration of physiologic condition, polypharmacy and the high occurrence of chronic disease in elderly may manifest in oral cavity that can affect oral function. Objective : this study aimed to know was there any correlation and how was the correlation between oral health status and oral health-based quality of life of elderly community in Kodya Yogyakarta. Material and Method : data of this study were obtained from quality of life questioner modified from Dental Impact of Daily Living Index and from intraoral examination. Determination of oral health status based on examination of oral mucosal lesion amount, oral hygiene, DMFT index and periodontal tissue status. Results : results of this study showed that mean of DMFT index was 16.9 and 63% subjects were found with gingivitis, average of subject had moderate oral hygiene and each subject at least had two oral mucosal lesions. Mean score of quality of life was 27.2 and classified as satisfying. The data then were analyzed statistically using Pearson Product Moment Correlation and showed that from four parameters used to determine the oral health status, oral hygiene and amount of oral mucosal lesion had correlation with quality of life with r were -0.236 (P-value was 0.045) and -0.288 (P-value was 0.045), respectively. In high educated elderly group demonstrated that amount of oral mucosal lesion and oral hygiene had moderate and strong correlations with quality of life with r were -0.554 (P-value was 0.011) and -0.649 (P-value was 0.002), respectively. Conclusion : it can be concluded that oral health status correlates with oral health based-quality of life of elderly community in Kodya Yogyakarta.